Discrepancies between subjective and objective sleep assessments revealed by in-home electroencephalography during real-world sleep - Minori Masaki; Saki Tsumoto; Akihiro Tani; Morie Tominaga; Jaehoon Seol; Shigeru Chiba; Kazuya Miyanishi; Kei Nishida; Fusae Kawana; Takashi Amemiya; Tetsuro Hiei; Takashi Kanbayashi; et al. (Proceedings of the National Academy of Sciences, 2025)
Sleep insufficiency and sleep disorders pose serious health challenges. This study aimed to determine the potential discrepancy between subjective and objective sleep assessments, including the latter made by physicians, by analyzing a 421-participant dataset in Japan comprising multiple nights of in-home sleep electroencephalogram (EEG) data and questionnaire responses on sleep habits or subjective experiences. We employed logistic regression models to examine which subjective and objective sleep parameters physicians are paying attention to when assessing sleep insufficiency, insomnia, sleep quality, and sleep apnea. Questionnaire responses, including subjective sleep assessments, exhibited poor performance predicting physicians’ assessments, whereas objective data demonstrated good predictive performance, indicating a discrepancy between subjective and objective sleep assessments. Although the in-home sleep EEG measurements had minimal first night effects, incorporating measurements over multiple nights can improve the detection of objective insomnia. Moreover, we found that participants with severe sleep insufficiency overestimated their sleep duration, whereas those with subjective insomnia but without objective insomnia underestimated it. Additionally, subjective sleep quality reflected sleep efficiency but not the frequency of short awakenings or objective sleep depth. In particular, the effects of apnea on objective sleep quality were not subjectively perceived. Collectively, our findings suggest that subjective sleep assessments alone are insufficient for evaluating sleep health and that health checkups and advice based on sleep EEG measurements may be useful in improving sleep habits and for early detection of sleep disorders.